Anaphylactic shock with methylprednisolone, Kounis syndrome and hypersensitivity to corticosteroids: a clinical paradox - Nicholas G. Kounis; Ioanna Koniari; George D. Soufras; Emmanouil Chourdakis (BMC, 2018)
Abstract Corticosteroids are widely used for the treatment of allergic reactions but paradoxically themselves may induce acute, delayed, local or systemic allergic reactions and even anaphylaxis with Kounis syndrome. They can suppress the release of arachidonic acid from mast cell membranes, via phospholipase A2 and eicosanoid biosynthesis inhibition. Corticosteroids can promote cell apoptosis and mediate in annexin or lipocortin synthesis, substances that modulate inflammatory cell activation, adhesion molecule expression, transmigratory and phagocytic functions. Antigen-antibody reaction, hapten formation, and medication contaminants are some of the incriminated causes. Patients with atopic diathesis are particularly vulnerable. Complete and thorough previous history of drug reactions or allergies is necessary before administration of any particular medication including corticosteroids.